Women Count: Gender (in-)equalities in the human capital development in Asia, 1900-60 - Julia Friesen; Jörg Baten; Valeria Prayon (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
This paper traces the human capital development of 14 Asian countries for the period of 1900-60, using the age-heaping method. We place special emphasis on the gender gap in numeracy and its determinants. In particular, we test the validity of a U-hypothesis of gender equality, implying that gender equality in numeracy declines at initial stages of development and increases again with higher numeracy levels. The U-shaped pattern is strongly confirmed by our data.
urn:nbn:de:bsz:21-opus-60402
Keywords: I21; N35; O15; 330; human capital; age-heaping; education; gender inequality; numeracy; development; asia; Bildungsinvestition; Geschlechterdiskriminierung; Frauenbildung; Bildungsniveau; Entwicklungsstufe; Asien